Cases on forensic and criminological science for criminal detection and avoidance - Chaussée, Anna (Advances in digital crime, forensics, and cyber terrorism (ADCFCT) book series, 2024)
"This book covers an approach to forensic science as applied to the area of crime and criminal justice"--